Web-Based Design Of Tourism Object Information System In Bengkulu Selatan District - wendi harmansyah; kirman man; gunawan gunawan; surya saputra (Penerbit Jurnal Indonesia, 2023)
Along with the increasingly rapid development of technology, by seeing this potential, tourism promotion in South Bengkulu can utilize smartphones as a medium in providing tourism information in South Bengkulu to the public/smartphone users. Therefore, a website-based application was made for information facilities on tourist attractions in South Bengkulu. The research method used is by using interviews, observation, literature study and the system development method is requirement engineering, design, the stages of developing a tourist information system are implemented using the RAD (rapid application development) method. and testing. In making this website using xampp, MySql, PHP, client server and micromedia dreamweafer The result of making a website application at a tourist attraction in South Bengkulu is to provide information for users or tourists in finding information about tourism, culture and arts.